Detection and Confirmation of Mycoplasma pneumoniae in Urogenital Specimens by PCR - Sharma, S. (American Society for Microbiology, 1998)
Following the isolation of Mycoplasma pneumoniae from urogenital specimens (M. Goulet, R. Dular, J. G. Tully, G. Billows, and S. Kasatiya, J. Clin. Microbiol. 33:2823–2825, 1995), a study was undertaken to confirm the observations by PCR. Specific primers directed to the P1 adhesin gene of M. pneumoniae were used. A total of 300 genital specimens were tested for M. pneumoniae and Mycoplasma genitalium by culture and PCR. Of these, 15 were positive by culture and 17 were positive by PCR for M. pneumoniae. No M. genitalium was detected in any of the specimens by either method. The present study demonstrates that PCR is sensitive and rapid compared to cumbersome culture methods and can be used to detect M. pneumoniae in urogenital specimens in a routine diagnostic laboratory.